Problems and Prospects of Potato Cultivation in Bangladesh - Chowdhury, Muktasha Deena; Chowdhury, Anupam Hayath (Asian Business Review, 2015)
Bangladesh is predominantly an agricultural country. Agriculture is the indispensable culture of Bangladesh. Agriculture has an enceinte contribution to the Gross Domestic Product (GDP) of the country. Earlier more than 50% of GDP came from this sector. Various types of crops are produced in this country. These crops can be categorized into two; food crops and cash crops. Potato is one of the food-stuff of the most people of the world as well as Bangladesh. Potato crop is being treated as foremost crop. This research was conducted to find out the problems that the farmers face in cultivation and to study the trend of production of potato and relationship between production and export of potato of Bangladesh. The study also aims to show the estimates of potato per division in Bangladesh and thus to help in showing its prospects. This research is quantitative in nature. Data collected from both primary and secondary data sources. Primary data collected from 50 farmers using convenience sampling technique with a set of questionnaires designed for this study. Secondary data is obtained from secondary data sources, Department of Agricultural Extension (DAE) and BBS (Bangladesh Bureau of Statistics). After collecting the data, they were transcribed, tabulated and analysed in terms of the research objectives.